Education, turism and natural resources of Region Callao - Alcántara Boza, Alejandro (2010)
The participaties of education in the conservation of natural resources, especially of those who have access spaces such as the Natural Resources Land Surface (ERNAST) of the Callao region, involved at first instance to determine its existence, its location and identification resource type. For this it was counted with the participation of a sample of 73 teachers in the area of Science, Technology and Environment (CTA) of the Callao region, with the collection of cross-sectional data, whose objectives were specifically aimed at identifying the ERNAST in their relationship with education and tourism. Among the findings it was found that: 38% of the total area of the Callao region, corresponds to free areas, according the database 2004, with follow-up studies and space travel in 2006 and 2007; likewise the 53.4% of teachers in the sample believes there are few areas with exploitable natural resources for education, another 38.4% considered the areas of flora and space to develop scientific tourism, followed by the cliffs and beaches with a 32.9%.